Maradona’s Ghosts and Co.: Narrating Maradona in Argentine Football Literature. - Bertoglio, Carlos Andrés (Funes. Journal of narratives and social sciences, 2022)
When Roberto Santoro wrote Literatura de la pelota (1971) little did he imagined that this book, written from the margins of Argentine literature, would open a new literary path for a considerable number of ‘football writers’ in Argentina and Latin America. In the five decades that followed this seminal work, this genre has continued to grow and diversify. However, one key thematic element that has been periodically revisited in the Argentine context is that of the mythical concept of the pibe as a central reservoir of Argentine footballing identity and the figure of Maradona as its most perfect incarnation. This essay will attempt to, on the one hand, describe and illustrate the pibe-Maradona connection in the context of Argentine Football Fiction and on the other, explain the pivotal role of Maradona and that of his phantasmatic presence as fundamental components to approach this literary subgenre in the Argentine context.